STUDY OF ELECTRONIC KEY WITH GALVANIC ISOLATION - Krisan, Y. A.; Krisan, A. A. (Radio Electronics, Computer Science, Control, 2024)
The electronic key used as a high-speed threshold element with a galvanic outcome – the electronic relay for the control of a devices condition over semi-conductor converters which meets the basic requirements shown to devices of the control is offered.